Pengaruh Harga dan Kualitas Produk terhadap Kepuasan Pelanggan: Studi pada Pembeli Produk Eiger melalui Platform Shopee - Intan Aulia Salsabila; Rini Hidayah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The development of e-commerce in Indonesia has changed consumer behavior in purchasing products online, including Eiger products on Shopee. This study aims to determine the effect of price and product quality on customer satisfaction of Eiger products on Shopee using a quantitative method with a sample of 144 respondents who had purchased Eiger products through Shopee. Data were collected through Likert scale questionnaires and analyzed using SPSS 26 with validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination tests. The results showed that all data were valid and reliable, normally distributed, free from multicollinearity, and showed no heteroscedasticity, indicating that the research model was appropriate for use. The t-test results showed that price had no significant effect on customer satisfaction with a significance value of 0.339, while product quality had a positive and significant effect on customer satisfaction with a significance value of 0.000. The F-test results indicated that price and product quality simultaneously had a significant effect on customer satisfaction with a significance value of 0.000. The Adjusted R Square value of 64.6% indicates that customer satisfaction can be explained by price and product quality variables, while the remaining percentage is influenced by other factors outside this study. This study concludes that product quality is the main factor in increasing customer satisfaction, therefore Eiger needs to maintain its product quality to keep customer satisfaction well maintained.